Monetary and labor policies under market frictions - Christian Merkl (Universität Kiel, 2007)
The thesis analyzes monetary and labor policies under different market frictions. In the first part several versions of a microfounded dynamic general equilibrium model with monopolistic competitors in the product and/or labor market are derived and simulated. First of all, the monetary persistence of a pure price staggering economy is compared to a pure wage staggering economy under different labor market structures (by means of a newly proposed persistence measure) and interactions are explored. Secondly, the thesis simulates the effects of real wage rigidities in a disinflation experiment non-linearly. Thereby, caveats of the conventionally used log-linearization are shown. The second part of the thesis develops a dynamic microfounded labor market framework with insider wage bargaining, labor turnovers costs and tax distortions. The calibrated model is used in order to analyze different labor market policies. The addressed questions include the labor market development in East Germany after unification, the existence of unemployment traps, their influence on labor market persistence and policy effectiveness, and the optimal targeting of employment subsidies in terms of their employment, equity and welfare implications.
urn:nbn:de:gbv:8-diss-20914
Keywords: 330; Arbeitsmarkttheorie; Preisrigidität; Lohnrigidität; Unvollkommener Wettbewerb; Ungleichgewichtstheorie; Inflationsbekämpfung; Arbeitslosigkeit; Hysteresis; Lohnbildung; Lohnsubvention; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Theorie; Neue Bundesländer